Curriculum's role in fostering inter group contacts among the multiracial students in a secondary school in Johor Bahru [electronic resource] - 282119 Zawiyah Kaderi (2008)
Thesis (Sarjana Pendidikan (Kurikulum dan Pengajaran)) - Universiti Teknologi Malaysia, 2008